Cultural differences in visual perceptual learning. (14th December 2021) - Chua, Stephanie Y. P.; Rentzelas, Panagiotis; Frangou, Polytimi; Kourtzi, Zoe; Lintern, Maxine; Mavritsaki, Eirini
Abstract : Cultural differences in visual perceptual learning (VPL) could be attributed to differences in the way that people from individualistic and collectivistic cultures preferentially attend to local objects (analytic) or global contexts (holistic). Indeed, individuals from different cultural backgrounds can adopt distinct processing styles and learn to differentially construct meaning from the environment. Therefore, the present work investigates if cross‐cultural differences in VPL can vary as a function of holistic processing. A shape discrimination task was used to investigate whether the individualistic versus collectivistic backgrounds of individuals affected the detection of global shapes embedded in cluttered backgrounds. Seventy‐seven participants—including Asian (collectivistic background) and European (individualistic background) students—were trained to discriminate between radial and concentric patterns. Singelis's self‐construal scale was also used to assess whether differences in learning could be attributed to independent or interdependent self‐construal. Results showed that collectivists had faster learning rates and better accuracy performance than individualists following training—thereby reflecting their tendency to attend holistically when learning to extract global forms. Further, we observed a negative association between independent self‐construal—which has previously been linked to analytic processing—with performance. This study provides insight into how socio‐cultural backgrounds affect VPL.